Mapping the Ca2+ induced structural change in calreticulin - Boelt, Sanne Grundvad; Norn, Christoffer; Rasmussen, Morten Ib; André, Ingemar; Čiplys, Evaldas; Slibinskas, Rimantas; Houen, Gunnar; Højrup, Peter (Journal of proteomics, 2016)
Calreticulin is a highly conserved multifunctional protein implicated in many different biological systems and has therefore been the subject of intensive research. It is primarily present in the endoplasmatic reticulum where its main functions are to regulate Ca2+ homeostasis, act as a chaperone and stabilize the MHC class I peptide-loading complex. Although several high-resolution structures of calreticulin exist, these only cover three-quarters of the entire protein leaving the extended structures unsolved. Additionally, the structure of calreticulin is influenced by the presence of Ca2+. The conformational changes induced by Ca2+ have not been determined yet as they are hard to study with traditional approaches. Here, we investigated the Ca2+-induced conformational changes with a combination of chemical cross-linking, mass spectrometry, bioinformatics analysis and modelling in Rosetta. Using a bifunctional linker, we found a large Ca2+-induced change to the cross-linking pattern in calreticulin. Our results are consistent with a high flexibility in the P-loop, a stabilization of the acidic C-terminal and a relatively close interaction of the P-loop and the acidic C-terminal. The function of calreticulin, an endoplasmatic reticulin chaperone, is affected by fluctuations in Ca2+concentration, but the structural mechanism is unknown. The present work suggests that Ca2+-dependent regulation is caused by different conformations of a long proline-rich loop that changes the accessibility to the peptide/lectin-binding site. Our results indicate that the binding of Ca2+ to calreticulin may thus not only just be a question of Ca2+ storage but is likely to have an impact on the chaperone activity. [Display omitted] •Conformational changes of calreticulin can be monitored by cross-linking and MS.•The location of the P-loop is dependent on the concentration of Ca2+.•Part of the disordered acidic C-terminal is stabilized by Ca2+.